KEPENTINGAN TIONGKOK DALAM PROYEK BELT AND ROAD INITIATIVE (BRI) DI REPUBLIK DEMOKRATIK KONGO (RD KONGO) TAHUN 2021-2024 - Calfin Justinus Sidabariba; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
This research analyzes China's strategic interests in implementing the Belt and Road Initiative (BRI) project in the Democratic Republic of the Congo (DRC) during the 2021-2024 period. The study is motivated by the anomaly in China's foreign policy, which continues to inject massive investments into DR Congo's mining and infrastructure sectors despite the country's high political vulnerability and armed conflict risks. Utilizing a qualitative approach and document study method, this research investigates the strategic calculations behind this anomaly through the frameworks of classical realism, rational actor theory, and the concept of national interest. The findings reveal that the implementation of the BRI in DR Congo is not merely a form of development cooperation, but an asymmetric geostrategic instrument driven by two primary Chinese national interests. First, economic well-being interests manifested in efforts to monopolize the upstream and downstream supply chains of critical minerals to sustain its domestic green technology industry, while simultaneously eliminating geoeconomic competition from the Western Bloc, such as the Lobito Corridor initiative. Second, security interests realized through the private securitization of mining assets by co-opting local military security forces (FARDC), expanding military diplomacy, and protecting global logistics routes. In conclusion, the integration of geoeconomic expansion and asset securitization through the BRI project solidifies DR Congo as a vital subordinate satellite state to ensure the sustainability of China's raw material supply and geopolitical supremacy. Keywords: Belt and Road Initiative, China, Democratic Republic of the Congo, National Interest, Critical Minerals.